MANAJEMEN KONFLIK PAPUA MELALUI PENDEKATAN BIROKRASI PERWAKILAN: Analisis Representasi Deskriptif dan Substantif - Andhika Purbakala Rona; Tabah Maryanah (Halu Oleo University, 2024)
This research aims to analyze conflict management in Papua through a representative bureaucracy theory approach which prioritizes descriptive and substantive representation in managing social and political diversity. The prolonged conflict in Papua which is rooted in social injustice, discrimination and marginalization has encouraged feelings of marginalization and demands for independence. Even though the Indonesian government has implemented various policies to reduce conflict, such as granting special autonomy and increasing Papuan representation in the bureaucracy, serious challenges remain. This research uses a qualitative descriptive method with a case study approach to explore this phenomenon in more depth, by collecting data through in-depth interviews, observations and documentation studies related to Papuan policies. The data obtained was analyzed using thematic analysis to identify the main themes related to political representation and government policies in resolving conflicts. The research results show that although there have been significant efforts to achieve more inclusive political representation, the success of these policies is highly dependent on serious implementation that focuses on social justice and transparency. A representative bureaucratic approach, if applied with consistent principles, can make an important contribution to reducing social tensions and creating sustainable peace in Papua.